Educational psychology and educational practices mediated by ICT: State of the art - Juan Manuel Baquero Bonilla; Raúl Abarca Astete; Yasser Abarca Sánchez;Santiago Restrepo-Restrepo; Noemi Teresa Julca-Vera, Julián Leonardo Riveros Cruz (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A documentary review was carried out on publications in high impact journals indexed in the Scopus database related to Psychology in Education and Educational Practices mediated by ICT during the period 2010-2020. As a result of the first search, a total of 715 documents were classified according to their year of publication, country of origin, area of knowledge, authors and type of publication. In this way, the essential characteristics of the publications on the above-mentioned topic were identified. Similarly, the position of different authors was analyzed from a qualitative perspective through their research on educational practices mediated by ICT and psychology in education. The main findings of this paper are: The United States is the country with the highest number of publications registering a total of 260 research papers published during the period between the years 2010 and 2020, of which, the year with the highest number of records was 2020 with 130 publications. Of the total number of identified documents, 225 are made under theories that frame the social sciences and the most frequent type of publication for the authors was the journal paper, 75% of the total scientific production being published by this means. Thanks to the above, the final document is constructed through conclusions that could constitute support material for future research related to the topic proposed in this document.